Caring for Family Members With Alzheimer’s and Burnout Syndrome: Impairment of the Health of Housewives - Avargues-Navarro, María Luisa; Borda-Mas, Mercedes; Campos-Puente, Alina de las Mercedes; Pérez-San-Gregorio, María Ángeles; Martín-Rodríguez, Agustín; Sánchez-Martín, Milagrosa (Frontiers in Psychology, 2020)
Being a housewife may already be a psychosocial risk factor leading to chronic stress and burnout, and this may be aggravated when the housewife must also become the caregiver of a family member with Alzheimer’s. The burnout syndrome and how it can affect general health and the presence of emotional disorders were studied in housewives who were family caregivers of an Alzheimer’s patient. The sample selected was made up of 193 housewives, 96 of whom were also caregivers for a family member with Alzheimer’s. Sociodemographic measures used were the Maslach Burnout Inventory and The General Health Questionnaire. Burnout was found in a significant percentage of participants. Emotional exhaustion, effect on general health, and presence of emotional disorders were higher in caregivers. Emotional exhaustion, general health, and anxiety were more influential, while depersonalization affected the appearance of depressive symptoms more. Being a caregiver and emotional exhaustion appeared to be the best predictors of emotional disorders. It was confirmed that emotional exhaustion influenced appearance of anxiety and depression equally in both groups. In the case of caregivers, an exhaustion-illness spiral was produced. In this group, emotional exhaustion seemed to become more severe as a consequence of the presence of chronic illnesses, and possibly influence the number of hours spent on care and having children living at home. Future research should analyze in greater depth and in a larger sample, the role of these variables and widen the focus of attention to personal variables that could be acting as protective factors and could be subject to intervention. The discussion concludes with some actions that should be included in prevention programs for the groups studied.